Maxims of Cooperative Principle Found in The Disney Pixar Movie Elemental - Ni Luh Putu Bintang Aristya Canti; I Gusti Ayu Agung Sintha Satwika (RETORIKA: Jurnal Ilmu Bahasa, 2025)
To achieve the goal of effective communication, participants in a conversation must adhere to the cooperative principle. This study aims to examine the maxims of cooperative principle applied by the characters in an animated film that depicts differences in the characters' life backgrounds. The chosen film provides a rich context for exploring how language functions in characters’ interactions across cultural differences, thus this could be interesting to analyze in this topic.  This study employed a qualitative method. The data were obtained through observation and note-taking techniques. The observation method involved watching the Elemental movie on Disney+ Hotstar. The note-taking technique involved manually transcribing the script and categorizing the utterances, in accordance with Grice's (1975) theory of cooperative principle and Halliday and Hasan's (1985) context of situation. The discussion revealed that all four maxims of cooperative principle were found in the characters' utterances in the film. There were 42 maxims found in total, divided into four categories: 8 quantity maxims, 20 quality maxims, 7 relation maxims, and 7 manner maxims. A speaker still fulfills the maxim of manner, even if the utterance conveyed is not that brief, because the speaker is still in shock from what they have just experienced. The most frequently used maxim is quality, which indicates that the characters adhere to the truthfulness of information, whereas the least utilized maxims are relation and manner, which could be due to the diverse perspectives from each character's life backgrounds. This study shows that Elemental demonstrates clarity in communication is not only about grammatical accuracy; it involves emotional awareness and intentional expression. It enhances the nurtures mutual understanding across the differences among the Elemental characters and a good character development.